1995
DOI: 10.1111/j.1476-5381.1995.tb14918.x
|View full text |Cite
|
Sign up to set email alerts
|

Further analysis of the mechanisms underlying the tracheal relaxant action of SCA40

Abstract: 1 SCA40 (nM-1I0 LM), isoprenaline (1-300 nM) and levcromakalim (100 nM-10-IM) each produced concentration-dependent suppression of the spontaneous tone of guinea-pig isolated trachea. Propranolol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 20 publications
3
23
0
Order By: Relevance
“…However, they suggest that the interaction of SCA40 with the guinea pig trachea in vitro might be more complex than previously assumed. Thus, we found that suppression of the spontaneous tone of guinea pig trachea by SCA40 can be described by a biphasic rather than the monophasic concentration-response curves, as described by Cook et al 1995. The reason for this discrepancy is unclear.…”
Section: In Vitro Effectsmentioning
confidence: 64%
See 3 more Smart Citations
“…However, they suggest that the interaction of SCA40 with the guinea pig trachea in vitro might be more complex than previously assumed. Thus, we found that suppression of the spontaneous tone of guinea pig trachea by SCA40 can be described by a biphasic rather than the monophasic concentration-response curves, as described by Cook et al 1995. The reason for this discrepancy is unclear.…”
Section: In Vitro Effectsmentioning
confidence: 64%
“…Previous data have shown SCA40 to suppress both the spontaneous tone (Cook et al 1995) and the tone induced by various spasmogens McHarg et al 1994) in the isolated guinea pig trachea. The results of the current study confirm this property of SCA40.…”
Section: In Vitro Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, only a poor correlation between membrane hyperpolarization and relaxation has been noted in relaxation caused by fJ-adrenoceptor activation (Cook et al, 1993). Furthermore, there is evidence that the inhibitory action of charybdotoxin on isoprenaline-induced relaxation is due to an increase in Ca2+ influx through voltage-gated Ca2+ channels after membrane depolarization caused by the toxin (Huang et al, 1993 ;Cook et al, 1995 Bridsh Joumal of Phamacology (1995Phamacology ( ) 116, 2738Phamacology ( -2742 Tension and membrane potential recordings…”
Section: Introductionmentioning
confidence: 99%